2019
DOI: 10.1007/s00894-019-4146-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopy, and theoretical calculations of some 2-thiohydantoin derivatives as possible new fungicides

Abstract: We present the synthesis and structure determination for two thiohydantoin compounds (5-benzylidene-2sulfanylideneimidazolidin-4-one and 5-cinnamylidene-2-sulfanylideneimidazolidin-4-one), proposed as potential novel fungicides. The exact chemical structure of these molecules has not yet been determined since they can potentially exist in several tautomeric and geometric forms (Z-E isomerism). The geometries of all the theoretically possible structures of the studied compounds were optimised. The calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Noteworthy, a singlet NMR peak at 9.98 ppm corresponding to the proton from the thioamide (H–N–C S) segment of the T NH tautomer. 48 Conversely, the appearance of a 1.85 ppm S–H singlet peak in the deuterated solution of thiohydantoin revealed that the T SH tautomer had a role in maintaining the equilibrium of the ligand's tautomers. 48 Using the NH/SH peak intensity ratio, we may deduce that the core backbone of 4b exists in solution mostly as the thiol form (T SH ) (55%), with some input from the thione form (T NH ) (45%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Noteworthy, a singlet NMR peak at 9.98 ppm corresponding to the proton from the thioamide (H–N–C S) segment of the T NH tautomer. 48 Conversely, the appearance of a 1.85 ppm S–H singlet peak in the deuterated solution of thiohydantoin revealed that the T SH tautomer had a role in maintaining the equilibrium of the ligand's tautomers. 48 Using the NH/SH peak intensity ratio, we may deduce that the core backbone of 4b exists in solution mostly as the thiol form (T SH ) (55%), with some input from the thione form (T NH ) (45%).…”
Section: Resultsmentioning
confidence: 99%
“… 48 Conversely, the appearance of a 1.85 ppm S–H singlet peak in the deuterated solution of thiohydantoin revealed that the T SH tautomer had a role in maintaining the equilibrium of the ligand's tautomers. 48 Using the NH/SH peak intensity ratio, we may deduce that the core backbone of 4b exists in solution mostly as the thiol form (T SH ) (55%), with some input from the thione form (T NH ) (45%). Meanwhile, 13 C NMR spectroscopy gives more proof for the co-existence of the TSH and TNH tautomeric forms in these thiohydantoin solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiohydantoins have emerged as an important class of compounds due to their biological activity, [68][69][70][71][72][73][74] with particular focus on the antiparasitic behavior. [75][76][77][78] Wowk and Pavanelli explored the antileishmanial (L. amazonensis) effect, determining the key mechanism presented in parasite death, of various thiohydantoins bearing an acetyl group at the N1-position of the heterocyclic ring.…”
Section: Amino Acid-based Compoundsmentioning
confidence: 99%
“…For these reasons, NMR spectroscopy is highly sought after in drug development [ 37 , 38 , 39 , 40 , 41 ], for both molecule identification [ 11 , 13 , 14 , 18 , 42 , 43 , 44 , 45 , 46 ] and structural elucidation [ 15 , 16 , 17 , 45 , 47 , 48 , 49 , 50 , 51 ]. NMR has been successfully applied in stereochemistry [ 52 , 53 , 54 , 55 , 56 ] and isomer determination [ 57 , 58 , 59 , 60 , 61 ], in drug-protein interactions studies [ 62 , 63 , 64 ], and in the evaluation of drug toxicity [ 65 , 66 , 67 , 68 ].…”
Section: Introductionmentioning
confidence: 99%